Pathways of Persuasion: Unravelling Narrative Dynamics in Thailand's 2023 General Election - Surachanee Sriyai; Akkaranai Kwanyou (Journal of Current Southeast Asian Affairs)
This article embarks on unravelling the intricate narrative dynamics and ideological shifts that characterised Thailand's pivotal 2023 general election. Drawing inspiration from the extensive literature on political communication, we tracked the online activities of the ten most prominent political parties from one month prior to the election to two days afterward. Leveraging an original dataset comprising over 2500 posts disseminated by major parties on social media within that timeframe, the findings show that while parties have different posting strategies and predetermined platforms of choice, their campaign narratives can generally be categorised into five distinct groups. We only found partial support to the conventional assumption that voters tend to prioritise their own financial wellbeing. Although economic and populist policies are the most prevalent campaigning narratives for most political parties, the victory of the Move Forward party suggested that promises to address deep-rooted societal issues became more appealing to the Thai voters.